2022
DOI: 10.1091/mbc.e22-02-0037
|View full text |Cite
|
Sign up to set email alerts
|

ZC3HC1 is a structural element of the nuclear basket effecting interlinkage of TPR polypeptides

Abstract: The nuclear basket (NB) is a fibrillar structure commonly looked upon as solely built of polypeptides of the large coiled-coil-forming protein TPR. Here, protein ZC3HC1 is reported as a novel second structural element of the NB functioning in the stepwise recruitment and stable interconnection of TPR subpopulations at the NB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 78 publications
(86 reference statements)
2
27
0
Order By: Relevance
“…Altogether, such a reduction in the NE-associated amounts of Mlp1p, accompanied by a nucleoplasmic pool of Mlp1p due to Pml39p deficiency, resembled the effects we had by then noted in human cells, in which knockdown of ZC3HC1 by RNAi had caused a reduction in the NE-associated amounts of TPR, accompanied by a nucleoplasmic pool of TPR. Later, such findings also turned out in line with very similar results in ZC3HC1 KO cells (Gunkel et al, 2021) and eventually upon degron-mediated ZC3HC1 degradation too (Gunkel & Cordes, 2022), with the latter findings now also resembling the outcome of a study in which degronmediated degradation of Pml39p is shown affecting the NE-association of Mlp1p (Bensidoun et al, 2021b).…”
Section: Scpml39p As the Budding Yeast Homolog Of Hszc3hc1 Is Require...supporting
confidence: 76%
See 4 more Smart Citations
“…Altogether, such a reduction in the NE-associated amounts of Mlp1p, accompanied by a nucleoplasmic pool of Mlp1p due to Pml39p deficiency, resembled the effects we had by then noted in human cells, in which knockdown of ZC3HC1 by RNAi had caused a reduction in the NE-associated amounts of TPR, accompanied by a nucleoplasmic pool of TPR. Later, such findings also turned out in line with very similar results in ZC3HC1 KO cells (Gunkel et al, 2021) and eventually upon degron-mediated ZC3HC1 degradation too (Gunkel & Cordes, 2022), with the latter findings now also resembling the outcome of a study in which degronmediated degradation of Pml39p is shown affecting the NE-association of Mlp1p (Bensidoun et al, 2021b).…”
Section: Scpml39p As the Budding Yeast Homolog Of Hszc3hc1 Is Require...supporting
confidence: 76%
“…We corroborated this conclusion experimentally by demonstrating that two other species’ NuBaID-signature-containing proteins are true homologs of Hs ZC3HC1, namely a NuBaID-containing protein of Dictyostelium discoideum and the Pml39 protein of Saccharomyces cerevisiae , with these proteins together with Hs ZC3HC1 markedly exemplifying the diversity between the NuBaID proteins of different phyla. While Sc Pml39p had already been found to be an Mlp1/2-binding protein (Palancade et al , 2005) and recently stated to be the yeast homolog of Hs ZC3HC1 (Gunkel et al , 2021; Gunkel & Cordes, 2022), we here present the experimental evidence unveiling that Sc Pml39p just like Hs ZC3HC1 possesses a bimodular NuBaID and requires integrity of its NuBaID’s two modules for NB- and Mlp-interaction. Moreover, we demonstrate that NB-association of Pml39p is a prerequisite for the positioning of additional amounts of Mlp1p at the yeast’s NBs and that Pml39p even enables interconnections between Mlp1 polypeptides at sites remote from the NB.…”
Section: Introductionmentioning
confidence: 53%
See 3 more Smart Citations